British Association of Dermatologists guidelines for the management of people with cutaneous lupus erythematosus 2021. (1st December 2021) - O'Kane, D.; McCourt, C.; Meggitt, S.; D'Cruz, D.P.; Orteu, C.H.; Benton, E.; Wahie, S.; Utton, S.; Hashme, M.; Mohd Mustapa, M.F.; Exton, L.S.; ,
Abstract: Linked Comment: B.F. Chong. Br J Dermatol 2021; 185 :1084 .